Análise do perfil metabolômico diferencial de mudas de Eucalyptus urograndis submetidas a estresse hídrico - Silva, Fabrício Lelis da (2016)
The worsening of climate change and global population growth causes a gradual increase in global demand for water, either for direct human consumption or for food production in general. Agricultural production consumes about 70% of the entire water that is used on the planet, therefore, it has been the subject of many studies worldwide the discovery of adaptive water restrictions, aiming to implement them in species of agronomic interest. Verifying the importance of forestry activities in the national economy, especially the Eucalyptus genus, and also the existence of clones with different levels of tolerance to water stress, it is vital to understand the mechanisms used by plants in response to this stress. Intending to study these mechanisms and the search for genes related to water stress, several studies are conducted either in vitro or ex vitro. Were evaluated the use of sand as a substrate for ex vitro experiments with eucalyptus seedlings and its ability to simulate conditions of water stress, have been reached potential values ranging from -0.036 kPa in the control group, and -1500 kPa, in the intermediate stress group. For all stress points were evaluated morphological conditions of eucalyptus seedlings. During the study of metabolites produced in plants submitted to different levels of water restriction was observed by means Liquid Chromatography coupled to Mass Spectrometry (LC-MS), the existence of forty possible responsive molecules to stress, which, according with statistical analyzes, nine were identified as effectively responsive to water stress. Among these molecules are: 6-fosfoglucônico acid, which decrease in concentration allows associating the drop in metabolic rate; indoline, probably related to catabolic pathways involving indole-acetic acid (IAA), in the form of the species coupled between EIAPhenylalanine; the valine amino acid, phenyl-β-D-glucopyranoside and ptoluoyl-β-D-glucopyranoside, probably associated with combat reactive oxygen species. Besides these, other potential metabolites responsive to water stress were found and should be validated by further studies. All these mentioned compounds have the potential to act as stress level markers or used for prospecting for genetic mechanisms that may confer to plants of interest better adaptation to water stress.